1997
DOI: 10.1111/j.1399-3054.1997.tb01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal accumulation and ultrastructural localization of dehydrins in Zea mays

Abstract: Egerton-Warburton, L. M., Balsamo, R. A. and Close, T. J. 1997. Temporal accumulation and ultrastructural localization of dehydrins in Zea mays. -Physiol. Plant. 101: 545-555.Immunolocalization using polyclonal antibodies raised against a conserved dehydrin amino acid sequence was used to establish the temporal and spatial patterns of dehydrin accumulation in embryo tissue of Zea mays L. (var. Ohio 43) kernels imbibed in the presence of abscisic acid. The temporal pattem of accumulation indicated an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 24 publications
4
47
0
1
Order By: Relevance
“…The idea that DHNs interact with membranes is consistent with many immunolocalization studies, which have shown that DHNs accumulate near the plasma membrane or membrane-rich areas surrounding lipid and protein bodies (Asghar et al, 1994;Egerton-Warburton et al, 1997;Danyluk et al, 1998;Puhakainen et al, 2004). The K-segment is predicted to form a class A2 amphipathic a-helix, in which hydrophilic and hydrophobic residues are arranged on opposite faces (Close, 1996).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The idea that DHNs interact with membranes is consistent with many immunolocalization studies, which have shown that DHNs accumulate near the plasma membrane or membrane-rich areas surrounding lipid and protein bodies (Asghar et al, 1994;Egerton-Warburton et al, 1997;Danyluk et al, 1998;Puhakainen et al, 2004). The K-segment is predicted to form a class A2 amphipathic a-helix, in which hydrophilic and hydrophobic residues are arranged on opposite faces (Close, 1996).…”
supporting
confidence: 57%
“…For example, 13 Dhn genes have been identified in barley (Hordeum vulgare), dispersed over seven genetic map locations (Choi et al, 1999;Svensson et al, 2002) and regulated variably by drought, low temperature, and embryo development (Tommasini et al, 2008). DHNs are localized in various subcellular compartments, including cytosol (Roberts et al, 1993), nucleus (Houde et al, 1995), chloroplast (Artus et al, 1996), vacuole (Heyen et al, 2002), and proximal to the plasma membrane and protein bodies (Asghar et al, 1994;Egerton-Warburton et al, 1997;Puhakainen et al, 2004). Elevated expression of Dhn genes generally has been correlated with the acquisition of tolerance to abiotic stresses such as drought (Whitsitt et al, 1997), salt (Godoy et al, 1994;Jayaprakash et al, 1998), chilling (Ismail et al, 1999a), or freezing (Houde et al, 1995;Danyluk et al, 1998;Fowler et al, 2001).…”
mentioning
confidence: 99%
“…Subcellular localization data revealed that dehydrins are localized in various cell compartments including the cytosol, nucleus, vicinity of the plasma membrane, mitochondria and vacuole [34,35,37,[50][51][52]. However, they are primarily localized in the cytoplasm and nucleus.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…Many dehydrins were detected to accumulate in nucleus and even interact with DNA. This localization of dehydrins indicates stabilization of chromosome and protection of the transcriptional machinery (Carjuzaa et al 2008;Egerton-Warburton et al 1997;Hara et al 2009). Some dehydrins also accumulated in the vicinity of plasma membrane and were suggested to inhibit lipid peroxidation caused by ROS (Danyluk et al 1998).…”
Section: Many Studies Indicated That Plant Dehydrins Have Antioxidatimentioning
confidence: 94%